Mental Health First Aid Training for Health Care Workers in the Primary Health Care Center in Surabaya - Atika Dian Ariana; Tri Kurniati Ambarini; Dian Kartika Amelia Arbi (Proceedings Series on Social Sciences & Humanities, 2021)
The limitation of number of mental health professionals practicing at the primary health care center requires health care workers to be able to identify and intervene early in cases of mental disorders. Therefore, mental health first aid training for health care workers is needed. This research aims to examine the effectiveness of mental health first aid training to improve mental health literacy of the health care workers in the primary health care center. This was a simple randomized design with one group. The intervention was mental health first aid training which includes six sessions, namely mental health, mental health first aid, depression, anxiety, psychotics, and action plan. The training was attended by 58 health care workers and 1 staff from the Health Office of Surabaya. The instruments used were Mental Illness: Clinicians' Attitude Scale (MICA-4) to measure attitudes towards people with mental disorders and true-false questions to measure knowledge about mental health. The result of data analysis with paired-samples t-test showed that the mental health first aid training was effective in increasing the mental health literacy of health workers. Participants showed a significant increase in understanding of mental health (t = 3.575; p = 0.000). However, the limited opportunities for practice and direct interaction with mental patients affects the insignificant impact of training on changing attitudes towards people with mental disorders (t = -0.371; p = 0.753). Finally, this study recommends training methods that involve more practice in the future.